Implementing Malay traditional games in the classroom: A case study of young children in cultural art / Nur Faizah Che Me - Che Me, Nur Faizah (2013)
Play and games is a natural tendency of a child. ‘Play’ is a part of a child’s world where they would be able to choose games in a setting that would be fun and meaningful to them. I make the case that educational games can impact children in the developing world. In the context of primary school student aged from nine (9) years old, I report on a case study from one sub-urban community in the district of Ledang, Johor to show how game-based learning can help in creating a culturally meaningful learning environment in the classroom. This mixed method study involves 11 respondents which are students describing traditional village games that they play, and what they wish for during learning, based on my contextual interviews and distribution of questionnaires. The purpose of this case study is to understand the influences of reviving and implementing the Malay traditional games in the classroom during teaching and learning session and its effects toward students. Since the elements of traditional arts and its originality are marginalized, this paper also intended to identify the factors that contribute to the perceptiveness of students in comparison between Malay traditional games and digital games; and its significance towards the communities on a general level. This study also aimed to investigate about the acceptance issue of Malay gaming from the perspectives of primary school students through the lens of cultural arts. I then generally analyze and compare the mechanics in these Malay traditional games against existing digital games to show what makes traditional games unique and suitable to be implemented in schools. My analysis has assisted me to interpret the already known playability issues that I observed through the study, and support me to outline the possible roles to conserve and preserve the traditional games in the context of the classroom, and pointing out the benefits of and obstacles to widespread Malay traditional game-based learning in enhancing the educational system.